183k views
0 votes
Help me answer all of them even the word problem

Help me answer all of them even the word problem-example-1

1 Answer

3 votes

Answer and Explanation:

When you raise a power to a power, you multiply the two exponents. As you can see,
(a^(m))^(n) = a^(mn) .

1.
(k^(4))^(5) = k^(4*5) = k^(20) . So, the answer is k^20

2.
(8^(2))^(7) = 8^(2*7) = 8^(14) . So, the answer is 8^14

3. When you have two items that you're taking the power of, you put the exponent on both terms. For example, here:


(4p^(4))^(3) = 4^(3) * p^(4*3) = 4^3 * p^(12) = 64p^(12) . So, the answer is 64p^12

User Altrim
by
6.0k points